Molecular Mechanisms and Physiology of Disease 2014
DOI: 10.1007/978-1-4939-0706-9_10
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Nanoparticles in Medicine and Their Potential Application in Asthma

Abstract: In an attempt to diagnose and treat highly complex and often heterogeneous diseases, research aims to utilise the modifi able properties of nano-sized particles. Properties such as size, shape, charge, hydrophobicity, and surface chemistry may be altered in order to facilitate and promote targeted cellular uptake. Following the fi rst FDA-approved nanotherapeutic in 1990, more than 40 have been marketed worldwide with multiple nano-based medicines currently in development. Despite promising results, translatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 142 publications
(169 reference statements)
0
2
0
Order By: Relevance
“… 12–14 Furthermore, nanotherapeutic has been promoted everywhere throughout the world after the first FDA affirmed nanotherapeutic in 1990, to build up different nano-based drugs. 15 …”
Section: Introductionmentioning
confidence: 99%
“… 12–14 Furthermore, nanotherapeutic has been promoted everywhere throughout the world after the first FDA affirmed nanotherapeutic in 1990, to build up different nano-based drugs. 15 …”
Section: Introductionmentioning
confidence: 99%
“…Interactions between cell/tissue systems and nanoparticles are no longer a surprise. According to [9], there is a link between respiratory illness, environmental exposure, and nano-sized particles. [10] recently published the results of another investigation on the addition of multi-walled carbon nanoparticles to the dynamics of water within a vertical Cleveland Z-staggered cavity, which demonstrated that raising the Reynold number increases the inertial force.…”
Section: Background Informationmentioning
confidence: 99%